Development of Web-Based Interactive Learning Media on Excretory System Materials to Increase Learning Interest - Nurul Kholiza Priani; Kartika Ratna Pertiwi (Jurnal Penelitian Pendidikan IPA, 2024)
Education today requires the utilization of increasingly sophisticated technology, which provides new effectiveness and innovation in learning. One of them is the development of interactive learning media to optimize classroom learning, which aims to increase interest in learning and can make it easier for students to understand learning materials. This media development uses research and development (R&D) with the development model ADDIE. The data collection technique uses a questionnaire, which is divided into a feasibility questionnaire (for media experts and material experts), a practicality (for biology teachers and student responses), and a learning interest questionnaire. The results obtained from feasibility and practicality are very good criteria, and the results of learning interest show a much higher average value in the experimental class (79.21) than the control class (62.26). In general, it can be concluded that learning media are feasible, practical, and effective for increasing learning interest